PIK3CA hotspot mutations in circulating tumor cells and paired circulating tumor DNA in breast cancer: a direct comparison study. Issue 12 (30th September 2019) - Tzanikou, Eleni; Markou, Athina; Politaki, Eleni; Koutsopoulos, Anastasios; Psyrri, Amanda; Mavroudis, Dimitris; Georgoulias, Vassilis; Lianidou, Evi
Abstract : Liquid biopsy analysis, mainly based on circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA), provides an extremely powerful tool for the molecular profiling of cancer patients in real time. In this study, we directly compared PIK3CA hotspot mutations (E545K, H1047R) in EpCAM‐positive CTCs and paired plasma‐ctDNA in breast cancer (BrCa). PIK3CA hotspot mutations in CTCs and ctDNA were analyzed using our previously developed highly sensitive (0.05%), specific, and validated assay in plasma‐ctDNA from 77 early and 73 metastatic BrCa patients and 40 healthy donors. We further analyzed and directly compared PIK3CA hotspot mutations in DNAs isolated from CellSearch ® cartridges (CTCs) and paired plasma‐ctDNA, in 56 cases of early and 27 cases of metastatic breast cancer, and 16 corresponding primary tumors. In plasma‐ctDNA, PIK3CA hotspot mutations were identified in 30/77(39.0%) early and 35/73(47.9%) metastatic BrCa cases; none (0/40, 0%) of the healthy donors' plasma‐ctDNA samples were positive. Our direct comparison study in DNAs isolated from CellSearch ® cartridges (CTCs) and paired plasma‐ctDNA from the same blood draws has shown a lack of concordance in early BrCa (27/56, 48.2%), while the concordance in the metastatic setting was higher (18/27, 66.6%). Our results were validated by ddPCR methodology, and the concordance between our assay and ddPCR for PIK3CA E545K hotspot mutation was 30/37 (81.1%). In many cases, PIK3CA hotspot mutations were detected in samples found to be negative for CTCs in CellSearch ® . Our data demonstrated for the first time that (a) PIK3CA hotspot mutations are present at high frequencies in CTCs isolated from CellSearch ® cartridges and paired plasma‐ctDNA both in early and metastatic BrCa, (b) the detection and concordance of PIK3CA hotspot mutations between plasma‐ctDNA and CTCs are higher in the metastatic setting, (c) PIK3CA mutational status significantly changes after therapeutic intervention, and (d) PIK3CA mutation detection in CTCs and plasma‐ctDNA provides complementary information. Abstract : Our direct comparison study on the presence of PIK3CA hotspot mutations (E545K, H1047R) in EpCAM‐positive CTCs and paired plasma‐ctDNA demonstrated for the first time that PIK3CA mutations are present at high frequencies in both CTCs and paired plasma‐ctDNA and that there is a high concordance in the metastatic setting. PIK3CA mutational status significantly changes after therapeutic intervention.